Coupled-driven high-speed and high-torque switchable transmission with a large transmission ratio - Toshio Takayama; Masaki Waragai (ROBOMECH Journal, 2023)
Abstract Electric motors are used globally, especially in industrial applications, and achieving high energy efficiency is a major problem. Variable transmissions are effective in reducing the energy consumption of motors, but practical variable transmissions are bulky and heavy, making them unsuitable for robots. To overcome this problem, two motor-driven mechanisms have been proposed. The two motors are operated independently and assigned to the high-speed drive and high-torque drive, and one motor always becomes dead weight. Therefore, we propose a coupled-driven switchable transmission system that can switch the high-speed and high-torque drives by combining the rotation directions and utilizing the output of both motors. The developed device uses two 22-W motors and can switch the reduction ratio from 1/15 to 1/375. The maximum torque, maximum rotation speed, and weight are 10 Nm, 500 rpm, and 905 g, respectively. The experimental results show that the relative speeds of two motors are significant for the coupled drive; nevertheless, this device can be controlled by conventional voltage control without precise speed control.